2022
DOI: 10.21203/rs.3.rs-1302080/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Exploring the perspectives of healthcare providers on providing HIV prevention and treatment services for Key Populations in Rwanda: a qualitative study.

Abstract: Background:The HIV prevalence and incidence among the general population in Rwanda have decreased significantly in the past decade, with only about 3% prevalence as of 2019. However, opposite trends are seen among the key populations (KP). The prevalence among commercial sex workers is as high as 51%, and the HIV rates among this group continue to rise. While the prevalence among key populations remains high, their adherence to HIV treatment is low compared to the general population. Healthcare providers play … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…The other study explored the perspectives of healthcare providers on providing HIV prevention and treatment services for key populations in Rwanda, found MSM and commercial sex workers experienced stigma within the communities and health facilities resulting in their delay to seek care (20). Similar stigma hampered access to healthcare services for key populations were found in sub-Saharan African region as well as neighboring countries including Uganda and Kenya (3,19,20,21,22).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The other study explored the perspectives of healthcare providers on providing HIV prevention and treatment services for key populations in Rwanda, found MSM and commercial sex workers experienced stigma within the communities and health facilities resulting in their delay to seek care (20). Similar stigma hampered access to healthcare services for key populations were found in sub-Saharan African region as well as neighboring countries including Uganda and Kenya (3,19,20,21,22).…”
Section: Discussionmentioning
confidence: 84%
“…Isano and colleagues in a 2019 study assessed the barriers to HIV post-exposure prophylaxis access among MSM in sub-Saharan Africa, reported that Rwandan MSM face rampant stigma and discrimination at various levels: family, community, and the healthcare settings which negatively impacted their healthcare seeking behavior (19). The other study explored the perspectives of healthcare providers on providing HIV prevention and treatment services for key populations in Rwanda, found MSM and commercial sex workers experienced stigma within the communities and health facilities resulting in their delay to seek care (20). Similar stigma hampered access to healthcare services for key populations were found in sub-Saharan African region as well as neighboring countries including Uganda and Kenya (3,19,20,21,22).…”
Section: Discussionmentioning
confidence: 99%
“…While the CBHI does cover multiple services, a lack of acceptance and potential of being disowned from their families has been noted across other studies in Rwanda as a notable impediment for these populations to obtain insurance coverage (21). The structural challenges that are propagated by inadequate insurance coverage for gender and sexual minorities have been well documented and can act as an impediment to care seeking behaviors, including HIV testing and treatment (22,22). Hence, individual insurance plans may be bene cial for gender and sexual minorities to ensure continued access to services despite societal stigma.…”
Section: Systemic Barriersmentioning
confidence: 99%